LELAGON LESTARI BUDAYAKU: GENDING PROPAGANDA BERBASIS SLOGAN - Raharja; Asep Saepudin; Siswati Siswati (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2025)
Lelagon Lestari Budayaku is a musical composition created as one of the selected pieces for the “2023 Inter-Regency/City Yogyakarta Women's Karawitan Festival